2019
DOI: 10.1088/1748-9326/ab5046
|View full text |Cite
|
Sign up to set email alerts
|

The aridity Index under global warming

Abstract: Aridity is a complex concept that ideally requires a comprehensive assessment of hydroclimatological and hydroecological variables to fully understand anticipated changes. A widely used (offline) impact model to assess projected changes in aridity is the aridity index (AI) (defined as the ratio of potential evaporation to precipitation), summarizing the aridity concept into a single number. Based on the AI, it was shown that aridity will generally increase under conditions of increased CO 2 and associated glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
138
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(145 citation statements)
references
References 47 publications
5
138
0
2
Order By: Relevance
“…Future studies may explore their potential physical mechanisms (i.e., connecting drought evolution with landatmosphere interactions). For other uncertainty sources, several previous studies Gu et al, 2019;Chen and Brissette, 2019) have been devoted to detecting and attributing uncertainty to GCM structure, RCPs, internal climate variability, and even drought indices. Here, it is challenging to consider all these uncertainties systematically; future work could focus on including the integrated uncertainty and quantifying relative contributions to drought evolution and impact assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies may explore their potential physical mechanisms (i.e., connecting drought evolution with landatmosphere interactions). For other uncertainty sources, several previous studies Gu et al, 2019;Chen and Brissette, 2019) have been devoted to detecting and attributing uncertainty to GCM structure, RCPs, internal climate variability, and even drought indices. Here, it is challenging to consider all these uncertainties systematically; future work could focus on including the integrated uncertainty and quantifying relative contributions to drought evolution and impact assessments.…”
Section: Discussionmentioning
confidence: 99%
“…The previous suggestions of more severe droughts largely arise from uncoupled modeling studies (Sheffield et al, 2012) that do not capture the various climate interactions and generally quantify droughts using potential evapotranspiration in addition to precipitation (Dai, 2013). Recent studies (Greve et al, 2019; Justin Sheffield et al, 2012; Milly & Dunne, 2016; Swann et al, 2016; Yang et al, 2019) have shown that these uncoupled approaches strongly overestimate regional drought and aridity increases due to inappropriate assumptions under increasing CO 2 and are inconsistent with coupled climate model projections. As such, those studies have encouraged the use of direct climate model outputs in drought assessments.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the debate on the role of AED on drought severity (B. Cook et al, 2018;Dai et al, 2018;Greve et al, 2019) originates mainly from the notion that the role of AED is complex, depending largely on the drought type (e.g., meteorological, hydrological, and environmental) and prevailing climatic conditions (S. M. Vicente-Serrano, McVicar, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As such, it is expected that the atmospheric CO 2 fertilization would increase plant water use efficiency (Milly & Dunne, 2016;Roderick et al, 2015;A. L. S. Swann et al, 2016), alleviate plant water demand (Abigail L. S. Swann, 2018), and reduce the stress corresponding to hydrological deficits (Greve et al, 2019). However, the impact of atmospheric CO 2 fertilization is still uncertain (Brodribb et al, 2020;S.…”
Section: Introductionmentioning
confidence: 99%